2021
DOI: 10.17582/journal.aavs/2021/9.11.1886.1894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dried Azolla on Growth Performance, Hematological, Biochemical, Antioxidant Parameters, and Economic Efficiency of Broiler Chickens

Abstract: P oultry industry becomes one of the most expanding sectors in the world as it helps to fulfill the gap between the requirement and the availability of high-quality protein for human consumption, leading to increase demand for higher and safer protein source (Alkhalf et al., 2010). Feed is considered the largest single production cost in broiler production and can constitute up to 80% of total livestock production costs and 86-87% of the total variable production cost (Davis et al., 2013). The shortage of fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
4
4
0
Order By: Relevance
“…Table (5) showed that the addition of Azolla(4.5,9,13.5)% did not significantly affect the rate of weight gain compared to control during the different breeding period, as well as the total weight gain, which respectively amounted to (3169.17, 2935.67, 3062.33, 2987.33) g for the treatments, respectively, and this is in line with the performance of birds in the rate Body weight (Table 3), relative growth (Table 4) and conversion factor (Table 7) with an improvement in economic indicators (Index, production coefficient and productivity per square meter, Table 9). These results agreed with the researcher [20,21] and these results differed with the researcher [1,22,2] Table (6) shows that the addition of Azolla at a rate of (4.5, 9, 13.5%) did not significantly affect the relative growth rate during the breeding weeks, and despite the absence of a significant effect of the replacement treatments, however, in the sixth week, the relative growth rate increased significantly for these treatments compared to the control (without replacement) where it reached (37.74, 34.84, 35.60) compared with (18%), as it gave an increase in growth by (19.75, 16.79, 17.60%) over the control treatment. And also the relative growth rates for the total education period (1 day -42 days), which amounted to (65.97, 64.78, 65.51, 65.75%), respectively Table (7) shows that there is a significant effect of the treatments of adding Azolla by (4.5,9,13.5)%, as it increased the feed consumption in the first two weeks of breeding compared to the control treatment, and with the age of the birds, we note the disappearance of this effect in the weeks of breeding and in the total consumed feed for the period ( 0-6) weeks, where it reached (4871.8, 5089.8, 4794.1, 5000.37) gm for the control treatment and for the addition treatments (3.5, 7.0, 9.5)%, respectively.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Table (5) showed that the addition of Azolla(4.5,9,13.5)% did not significantly affect the rate of weight gain compared to control during the different breeding period, as well as the total weight gain, which respectively amounted to (3169.17, 2935.67, 3062.33, 2987.33) g for the treatments, respectively, and this is in line with the performance of birds in the rate Body weight (Table 3), relative growth (Table 4) and conversion factor (Table 7) with an improvement in economic indicators (Index, production coefficient and productivity per square meter, Table 9). These results agreed with the researcher [20,21] and these results differed with the researcher [1,22,2] Table (6) shows that the addition of Azolla at a rate of (4.5, 9, 13.5%) did not significantly affect the relative growth rate during the breeding weeks, and despite the absence of a significant effect of the replacement treatments, however, in the sixth week, the relative growth rate increased significantly for these treatments compared to the control (without replacement) where it reached (37.74, 34.84, 35.60) compared with (18%), as it gave an increase in growth by (19.75, 16.79, 17.60%) over the control treatment. And also the relative growth rates for the total education period (1 day -42 days), which amounted to (65.97, 64.78, 65.51, 65.75%), respectively Table (7) shows that there is a significant effect of the treatments of adding Azolla by (4.5,9,13.5)%, as it increased the feed consumption in the first two weeks of breeding compared to the control treatment, and with the age of the birds, we note the disappearance of this effect in the weeks of breeding and in the total consumed feed for the period ( 0-6) weeks, where it reached (4871.8, 5089.8, 4794.1, 5000.37) gm for the control treatment and for the addition treatments (3.5, 7.0, 9.5)%, respectively.…”
Section: Resultssupporting
confidence: 87%
“…Table (8) showed that the addition of Azolla at a rate of (4.5, 9, 13.5)% to the diet did not significantly affect the feed conversion coefficient during the rearing weeks compared to the control, as well as the total conversion coefficient for the period (1 day -6 weeks), which amounted to (1.607, 1.627). , 1.607, 1.633) gm feed / gm weight gain, and the reason may be due to the fact that the Azolla protein was able to reach a benefit coefficient equal to the protein of the diet replaced by the feed, as it gave the same productive performance to the birds, and these results were in line with Table (3) regarding live body weight and Table (4) regarding weight gain and with the table (5) concerning the relative growth rate and agreed with [24,5,11,12,21] and it differed [26,25,27,14,1,16,18,12,22,20,2]. Significantly different letters indicate that there are significant differences between the means under the probability (p ≤ 0.05).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations